The Obstacles of Scientific Productivity Among Faculty Members at Palestine Technical University – kadoorei: Field Study - Al-Qasem, Hussam Husni; Abu Saa, Jafar Wasfi (Journal of Educational and Psychological Sciences, 2019)
This study aimed at investigating the obstacles of scientific productivity among faculty members at Palestine Technical University – kahdoorei, and identifying the effect of different variables of the study such as (Gender, Academic Rank, College, and Years of Experience) on the faculty members’ opinions about the obstacles of scientific productivity. The study was conducted during the second semester of the academic year (2018-2019) with an objective sample of (91) Individuals which represents (77%) of the study population which makes (118) members the faculty of the Technical University of Palestine. The two researchers developed a study instrument a questionnaire of (31) items which measures the obstacles of scientific productivity among faculty members of the Technical University of Palestine – kahdooreif. The validity and stability of the study instrument were verified with a stability coefficient of (0.92). The findings of this study indicated that the level of scientific productivity constraints among faculty members at the Technical University of Palestine- kahdoorei is generally high. The study also indicated that there were no statistically significant differences in the level of scientific productivity in the faculty of the Technical University of Palestine- kahdoorei attributed to the gender variable, the scientific rank, and the years of experience. The researchers of this study recommends that there is a need to provide a cadre of research assistants in the university laboratories; to reduce the academic load on faculty members when they are assigned administrative tasks, and to provide providing training courses for faculty members in the field of scientific research and language skills as well as the use of the Internet and global database.